Prevalence of Thrombocytosis in Children with Iron Deficiency Anemia - Khan, Naseemullah; Shahzad, Qamar Uz Zaman; Ramzan, Atiqa; Ali, Ayesha; Fatima, Kanwal; Ejaz , Feeza (Indus Journal of Bioscience Research, 2025)
Background: Iron deficiency anemia (IDA) is the most common nutritional deficiency in children and is often associated with hematological abnormalities beyond anemia itself, including reactive thrombocytosis. Objective: To determine the prevalence of thrombocytosis among children diagnosed with iron deficiency anemia and to analyze its association with demographic and clinical variables. Methods: This cross-sectional study was conducted at the Department of Pediatric Medicine, Shalamar Hospital, Lahore, over a defined period. A total of 200 children aged 1 to 12 years with diagnosed IDA were enrolled through non-probability consecutive sampling. Demographic and clinical data were collected using a structured proforma. Blood samples were analyzed for hemoglobin, serum ferritin, and platelet count. Results: The mean age of participants was 6.4 ± 3.1 years, and 54% were male. Thrombocytosis was found in 138 out of 200 children (69%). It was more common in children with serum ferritin <10 ng/mL (78.6%) compared to those with ≥10 ng/mL (56.8%) (p = 0.002). A significant association was also observed with socioeconomic status, with higher rates among children from low-income families (p = 0.03). No significant associations were found with age or gender. Conclusion: Thrombocytosis is a frequent finding in children with iron deficiency anemia, particularly among those with severe iron depletion and lower socioeconomic status. Clinicians should recognize this benign, reactive process to prevent unnecessary investigations and focus on timely nutritional management.